Apolipoprotein A-II induces acute-phase response associated AA amyloidosis in mice through conformational changes of plasma lipoprotein structure - Yang, Mu (Sci Rep, 2018)
During acute-phase response (APR), there is a dramatic increase in serum amyloid A (SAA) in plasma high density lipoproteins (HDL). Elevated SAA leads to reactive AA amyloidosis in animals and humans. Herein, we employed apolipoprotein A-II (ApoA-II) deficient (Apoa2(−/−)) and transgenic (Apoa2Tg) mice to investigate the potential roles of ApoA-II in lipoprotein particle formation and progression of AA amyloidosis during APR. AA amyloid deposition was suppressed in Apoa2(−/−) mice compared with wild type (WT) mice. During APR, Apoa2(−/−) mice exhibited significant suppression of serum SAA levels and hepatic Saa1 and Saa2 mRNA levels. Pathological investigation showed Apoa2(−/−) mice had less tissue damage and less inflammatory cell infiltration during APR. Total lipoproteins were markedly decreased in Apoa2(−/−) mice, while the ratio of HDL to low density lipoprotein (LDL) was also decreased. Both WT and Apoa2(−/−) mice showed increases in LDL and very large HDL during APR. SAA was distributed more widely in lipoprotein particles ranging from chylomicrons to very small HDL in Apoa2(−/−) mice. Our observations uncovered the critical roles of ApoA-II in inflammation, serum lipoprotein stability and AA amyloidosis morbidity, and prompt consideration of therapies for AA and other amyloidoses, whose precursor proteins are associated with circulating HDL particles.